Cyclooxygenase 1 (COX1) expression in Type 2 diabetes mellitus: A preliminary study from north India - Verma, Sushma; Chandra, Honey; Banerjee, Monisha (The Egyptian journal of medical human genetics, 2016)
The 6th edition of International Diabetes Federation, 2014 shows an estimate of 387 million people with Type 2 diabetes mellitus (T2DM) worldwide, expected to rise to 592 million by 2035. T2DM is a metabolic disorder, one of the reasons being oxidative stress due to impairment in antioxidant enzymes. It leads to several complications such as micro and macrovascular diseases. Cyclooxygenase1 (COX1) enzyme is the rate limiting factor for the arachidonic pathway leading to vascular wall contraction with angiotensin II occurring in heart diseases resulting from T2DM. COX1 determines 6-Keto Prostaglandin F1α (6-k-PGF1α) level, plays a major role in vasodilation and restricts macrophage platelet aggregation. The aim of the present study was to compare the COX1 expression and level of reactive oxygen species (ROS) in T2DM patients and controls at different time periods in human macrophages in order to find a biomarker or drug target. The study subjects consisted of 100 individuals, 50 each from T2DM patients and healthy sex/age matched controls. Cell proliferation by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and ROS measurement by 2′,7′-dichlorofluorescein diacetate (DCFDA) staining were performed at different time periods (24, 48, 72h). COX1 mRNA expression was checked by relative quantification method after real-time polymerase chain reaction (RT-PCR). The MTT assay showed that cell viability was significantly higher at 48h (P<0.05). ROS production was found to be lowest at 24h by DCFDA staining. ROS levels were raised in T2DM patients as compared to controls. The quantitative RT-PCR analysis showed that the COX1 expression was higher in T2DM patients as compared to healthy controls although not significant (P>0.05). Although COX1 is known to be a “housekeeping” gene, our study showed that its expression can be correlated with the disease condition and be used as a marker. However, further studies are required in more number of samples from other ethnic populations to confirm the findings.